Power quality improvement using Unified Power Quality Conditioner (UPQC) - Abd. Jalil, Ashrif (2019)
The purpose of this project is to evaluate the effectiveness of control strategy of Unified Power Quality Conditioner (UPQC) in order to improve power quality problem in distribution system specifically harmonics distortion. The performance of UPQC system controlled by Fuzzy Logic Controller (FLC) is compared by Proportional Integral (PI) controller. The control strategy depends on d-q transformation both shunt active filter and series active filter, phase-locked loop synchronization and constant dc-link voltage. The capability and performance of FLC and PI controller under non-linear load is demonstrated using test models built in Matlab / Simulink software. Simulation result is depicts the reliability of Fuzzy Logic Controller in reducing harmonics distortion in comparison with PI controller. The equipment is designed to have potential in reducing total harmonic distortion to values within the prescribed criteria set by IEEE standards.